Pengaruh Net Interest Margin, Non-Performing Loan, dan Capital Adequacy Ratio terhadap Stabilitas Perbankan di Industri Perbankan Terdaftar di BEI 2019-2023 - Inaya Tusifa; Reni Oktavia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The stability of the banking sector is crucial in maintaining a country’s financial system and economic sustainability. This study analyzes the impact of Net Interest Margin (NIM), Non-Performing Loans (NPL), and Capital Adequacy Ratio (CAR) on banking stability in Indonesia. The inconsistency of previous research findings indicates a research gap that requires further exploration. This study employs a quantitative approach using secondary data from financial reports of conventional banks listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The sample was selected using purposive sampling, resulting in 39 banks with 195 observations. Data analysis was conducted using multiple linear regression with classical assumption tests, including normality, heteroscedasticity, multicollinearity, and autocorrelation, to ensure model validity. The results show that NIM positively but not significantly affects banking stability, while NPL has a negative and significant effect. CAR also significantly influences banking stability. Enhancing banking intermediation effectiveness through NIM and CAR can strengthen financial stability, whereas increasing credit risk, reflected in NPL, can weaken stability. This study provides insights for regulators and banking management in designing more effective policies to maintain banking sector stability in Indonesia.